Bacterial Biofilm Growth on 3D-Printed Materials - Hall, Donald C.; Palmer, Phillip; Ji, Hai-Feng; Ehrlich, Garth D.; Król, Jarosław E. (Frontiers in Microbiology, 2021)
Recent advances in 3D printing have led to a rise in the use of 3D printed materials in prosthetics and external medical devices. These devices, while inexpensive, have not been adequately studied for their ability to resist biofouling and biofilm buildup. Bacterial biofilms are a major cause of biofouling in the medical field and, therefore, hospital-acquired, and medical device infections. These surface-attached bacteria are highly recalcitrant to conventional antimicrobial agents and result in chronic infections. During the COVID-19 pandemic, the U.S. Food and Drug Administration and medical officials have considered 3D printed medical devices as alternatives to conventional devices, due to manufacturing shortages. This abundant use of 3D printed devices in the medical fields warrants studies to assess the ability of different microorganisms to attach and colonize to such surfaces. In this study, we describe methods to determine bacterial biofouling and biofilm formation on 3D printed materials. We explored the biofilm-forming ability of multiple opportunistic pathogens commonly found on the human body including Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus to colonize eight commonly used polylactic acid (PLA) polymers. Biofilm quantification, surface topography, digital optical microscopy, and 3D projections were employed to better understand the bacterial attachment to 3D printed surfaces. We found that biofilm formation depends on surface structure, hydrophobicity, and that there was a wide range of antimicrobial properties among the tested polymers. We compared our tested materials with commercially available antimicrobial PLA polymers.